Theoretical Aspects of Learning Software State and Development Trends - Rustam Utkurovich Kuchkarbaev (International Journal on Orange Technologies, 2021)
In this article, students are provided with information about the preparation of the project "Analysis of LMS systems" for the course "Informatics and Information Technology", types of LMS systems, standards of LMS systems, advantages and functions of LMS systems, methods of their use, which universities use LMS systems, Analyzed data on sites created on the basis of LMS systems. This article analyzes LMS systems and focuses on solving learning management problems using the Moodle platform, which is the most popular of them.